Osteonecrosis of the jaw in patient with denosumab therapy - Olate, Sergio (Int J Clin Exp Med, 2014)
Osteonecrosis (ON) of the jaw has previously been linked to the use of biphosphonates; however, new drugs, also shown similar conditions. This article presents a female patient with mandibular ON related to the use of denosumab. The 55-year-old presented with bone exposure with 8 months of evolution after a dental extraction. The patient began subcutaneous injections of 60 mg denosumab four months prior to the extraction and the lesion remained after the procedure. The patient, with 14 months of follow-up, show mandible ON with no favorable evolution. The clinical condition is presented and the literature of ON associated with denosumab is discussed.